Investigations on the mortality in semi-fry seabass Lates calcarifer (Bloch) - Vartak, Vivek Rohidas; Makesh, M; Rajendran, K V; Sivakumar, N; Kumar, Kundan; Singh, Ravendrakumar (Indian Journal of Fisheries, 2012)
A study was undertaken to investigate the cause of mortality in semi-fry of wild collected Asian seabass Lates calcariferduring weaning on Artemia nauplii. The samples tested negative for nervous necrosis virus by PCR. On bacteriologicalanalysis Vibrio alginolyticus was isolated from kidney tissue of infected seabass. The pathogen identity was confirmed bybiochemical tests and further confirmed by automated bacterial identification system. The likely transmission of infectionmight be from rearing tanks or Artemia nauplii used for feeding semi-fry as they are considered to be the prime vectors ofthese bacteria.